IR and the false promise of philosophical foundations - Monteiro, Nuno P.; Ruby, Keven G. (International theory, 2009)
International Relations (IR) is uneasy about its status as a ‘science’. Throughout a long history of attempts to legitimate the field as ‘scientific’, IR scholars have imported multifarious positions from the Philosophy of Science (PoS) in order to ground IR on an unshakable foundation. Alas, no such unshakable foundation exists. The PoS is itself a contested field of study, in which no consensus exists on the proper foundation for science. By importing foundational divisions into IR, the ‘science’ debate splits the discipline into contending factions and justifies the absence of dialogue between them. As all foundations require a leap of faith, imperial foundational projects are always vulnerable to challenge and therefore unable to resolve the science question in IR. In this article, we seek to dissolve rather than solve the ‘science’ debate in IR and the quest for philosophical foundations. We argue that IR scholars should adopt an ‘attitude towards’ rather than a ‘position in’ the irresolvable foundational debate. Specifically, we advocate an attitude of ‘foundational prudence’ that is open-minded about what the PoS can offer IR, while precluding imperial foundational projects, which attempt to impose a single meta-theoretical framework on the discipline. This requires knowing what PoS arguments can and cannot do. As such, foundational prudence is post-foundational rather than anti-foundational. A prudent attitude towards philosophical foundations encourages theoretical and methodological pluralism, making room for a question-driven IR while de-escalating intra-disciplinary politics.